Vocal to local: indigenous dietary practices and diversity of wild food plants in Malai Mahadeswara wildlife sanctuary, South India - Harisha, PR; Gowthami, R; Siddappa Setty, R (Ethnobotany Research and Applications, 2021)
Background: The voice of the indigenous food system on locally available wild food plants and consumption is an important strategy to sustain interrelated food problems of malnutrition and disease. Methods: The study assessed the importance of wild food plant use among the forest-dwelling communities. Community perceptions were used to assess the patterns of use and interrelations of human well-being. Data was collected through a combination of semi-structured interviews, household surveys, and focus group discussions in eight villages. Local communities use wild plant species as food, therapeutic practices, and as a symbol of ethnic identity. Results: The taxonomical distribution and diversity of 126 species belonging to 94 genera and 58 families have been assessed. About 83% of wild leaves as greens fall in the category of weeds. There were 15 species WFPs that have been shared with neighbours in the village, close relatives, or friends. More than 28 species of leafy vegetables are used by 80% of households for more than 20 days a year. The local communities also use 120 wild edible herbs and root species in ethno-medicine. Boerhavia diffusa, Acacia farnesiana, and Alternanthera sissilis have been used frequently as vegetables, they were reported to reduce blood pressure, increase iron in the blood, and improve eyesight. Conclusions: The study emphasizes the dependency on the local food source and its livelihood importance. The study would help to evaluate the potential of WFPs use as future food in indigenous dietary systems and therapeutic practices. Keywords: Indigenous food system, dietary diversity, therapeutic value, wild food plants